Cumulative Weight Exposure Is Associated with Different Weight Loss Strategies and Weight Loss Success in Adults Age 50 or Above. (23rd June 2015) - Sénéchal, Martin; Slaght, Jana; Bouchard, Danielle R.
Abstract : Objectives . To evaluate if cumulative weight exposure is associated with weight loss strategy choices and weight loss success. Methods . Data from the National Health and Nutrition Examination Survey were used; a total of 4, 562 people age 50 years or older who reported trying to lose weight in the last year were studied. Cumulative weight exposure (CWE) score was defined as the sum of body mass index points above 25 kg/m 2 at the age of 25, 10 years ago, 1 year ago, and now. Weight loss strategies were self-reported and weight loss success was defined as reaching a 5% weight loss in the last year. Results . Chosen strategies for weight loss vary across tertiles of CWE. Participants in the highest CWE tertile were about 4 to 20 times more likely to lose at least 5% of body weight in the past year compared to those in the lowest CWE tertile (P < 0.05 ). Discussion . Strategies used to lose weight and weight loss success using different weight loss strategies vary considerably across cumulative weight exposure. Thus, cumulative weight exposure might be a variable worth considering when intervening with this population.